2017
DOI: 10.7759/cureus.1094
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of the Median and Radial Nerves at the Elbow: Application to Avoiding Injury During Venipuncture or Other Invasive Procedures of the Cubital Fossa

Abstract: IntroductionThe median and radial nerves are two important neural structures found in the cubital fossa. The trajectory and landmarks used to identify their location are important when procedures are done in this area.Methods and materialsTen fresh-frozen cadavers were dissected (20 upper limbs) and measurements were taken from the medial epicondyle to the median and radial nerves as well as to the lateral epicondyle of each limb.ResultsThe distance between the medial epicondyle and the median nerve was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…It is located medially to the brachial artery and deeply to the biceps tendon aponeurosis at the cubital fossa of the elbow. 31 When it enters the forearm, it passes between the heads of the pronator teres. 10 Husarik et al reported that the MN courses between the pronator teres muscle and the brachialis muscle, close to the vascular bundle in 83% of asymptomatic volunteers.…”
Section: Nervesmentioning
confidence: 99%
“…It is located medially to the brachial artery and deeply to the biceps tendon aponeurosis at the cubital fossa of the elbow. 31 When it enters the forearm, it passes between the heads of the pronator teres. 10 Husarik et al reported that the MN courses between the pronator teres muscle and the brachialis muscle, close to the vascular bundle in 83% of asymptomatic volunteers.…”
Section: Nervesmentioning
confidence: 99%
“…This technique allows excellent visual access to the joints and facets of the elbow. However, the neurovascular bundles traversing the elbow joint can be relatively easy prey to the instruments of the surgeon and detailed knowledge of the anatomy of the region is essential [ 15 , 16 ]. Nevertheless, injuries to the nerves traversing the elbow are surprisingly rare.…”
Section: Discussionmentioning
confidence: 99%
“…MN is an important neural structure in the CF which has to be identified during surgical procedures in order to avoid injuries. 3 Injury to the MN can lead to loss of flexion of hand. Various studies have been done to study the course and variation in the MN.…”
Section: Discussionmentioning
confidence: 99%